Vaccination with the variable tick protein of the relapsing fever spirochete Borrelia hermsii protects mice from infection by tick-bite. Issue 1 (December 2015) - Krajacich, Benjamin; Lopez, Job; Raffel, Sandra; Schwan, Tom
Abstract Background Tick-borne relapsing fevers of humans are caused by spirochetes that must adapt to both warm-blooded vertebrates and cold-blooded ticks. In western North America, most human cases of relapsing fever are caused byBorrelia hermsii, which cycles in nature between its tick vectorOrnithodoros hermsi and small mammals such as tree squirrels and chipmunks. These spirochetes alter their outer surface by switching off one of the bloodstream-associated variable major proteins (Vmps) they produce in mammals, and replacing it with the variable tick protein (Vtp) following their acquisition by ticks. Based on this reversion to Vtp in ticks, we produced experimental vaccines comprised on this protein and tested them in mice challenged by infected ticks. Methods Thevtp gene from two isolates ofB. hermsii that encoded antigenically distinct types of proteins were cloned, expressed, and the recombinant Vtp proteins were purified and used to vaccinate mice.Ornithodoros hermsi ticks that were infected with one of the two strains ofB. hermsii from which thevtp gene originated were used to challenge mice that received one of the two Vtp vaccines or only adjuvant. Mice were then followed for infection and seroconversion. Results The Vtp vaccines produced protective immune responses in mice challenged withO. hermsi ticks infected withB. hermsii . However, polymorphism in Vtp resulted in mice being protected only from the spirochete strain that produced the same Vtp used in the vaccine; mice challenged with spirochetes producing the antigenically different Vtp than the vaccine succumbed to infection. Conclusions We demonstrate that by having knowledge of the phenotypic changes made byB. hermsii as the spirochetes are acquired by ticks from infected mammals, an effective vaccine was developed that protected mice when challenged with infected ticks. However, the Vtp vaccines only protected mice from infection when challenged with that strain producing the identical Vtp. A vaccine containing multiple Vtp types may have promise as an oral vaccine for wild mammals if applied to geographic settings such as small islands where the mammal diversity is low and the Vtp types in theB. hermsii population are defined.